Experimental and numerical study on mechanical and fracture behavior of rock-like specimens containing pre-existing holes flaws. Issue 1 (2nd January 2022) - Zhao, Zhenlong; Jing, Hongwen; Shi, Xinshuai; Han, Guansheng
Abstract: Laboratory tests and numerical simulation are conducted to study mechanical behavior of rock containing two pre-existing holes in this paper. First of all, rock-like specimens containing two pre-existing holes were prepared to investigate mechanical and acoustic emission characteristics in the uniaxial compression. Different geometries were obtained by changing the angle of the center line of holes with respect to the direction of axial loading. Experimental results show that the stress-strain curves present obvious fluctuation, and evolution process of acoustic emission signal can be divided into four stages. There are three kinds of failure modes: only shear failure, mainly shear and auxiliary tensile failure, mainly tensile and auxiliary shear failure. Then, parallel bonded mode (PBM) based on the particle flow code in two dimensions (PFC 2D ) were established to study strength and failure modes in the biaxial compression. Finally, process of cracks initiation, propagation and coalescence, and fracture mechanism were further discussed. The most important conclusion reached is that the deformation and failure process of rock mass containing holes defects can be divided into two stages: rock bridge penetration and overall instability, which are sequential.